Comparing Some Methods For A single Imputed A missing Observation In Estimating Nonparametric Regression Function - نبيل, قتيبة; يوسف, مناف (Journal of Economics and Administrative Sciences, 2022)
In this paper, we will study non parametric model when the response variable have missing data (non response) in observations it under missing mechanisms MCAR, then we suggest Kernel-Based Non-Parametric Single-Imputation instead of missing value and compare it with Nearest Neighbor Imputation by using the simulation about some difference models and with difference cases as the sample size, variance and rate of missing data.